Comparison of Chest CT Findings between COVID-19 Pneumonia and Influenza Pneumonia - Masomeh Bayani; Mahsa Asadi; Naser Ghaemian; Mana Baziboroun (SINAPS LLC, 2023)
Introduction: With increasing global concerns about the prevalence of COVID-19, chest imaging findings are essential for effective diseases diagnosis and treatment. There is a need to distinguish between imaging features of COVID-19 pmeumonia and other viral pneumonia like Influenza.For this purpose, a study was performed on a comparison of chest CT findings between COVID-19 pneumonia and Influenza pneumonia. Methods: Fifty patients with respiratory symptoms and positive real-time PCR (RT-PCR) of nasopharyngeal swab for Influenza and fifty patients with respiratory symptoms and positive real-time PCR (RT-PCR) of nasopharyngeal swabfor COVID-19 from March to May 2020 were enrolled in the study. In the patient's checklist, information such as demographic characteristics (age, sex), laboratory findings including (CRP, ESR, WBC), and clinical signs (fever, cough, fatigue, dyspnea) were also recorded. Results: Gastrointestinal symptoms, anorexia, high CRP, ground-glass opacityare more common in patients with COVID-19 pneumonia than in patients with influenza pneumonia and this difference was statistically significant (P <0.05). But, fever is more common in influenza patients than in Covid-19 patients and this difference is statistically significant (P=0.029). The location of CT scan findings in COVID-19 patients was dominant in peripheral (54 %), while the location of CT scan findings in patients with Influenza was dominant in central (32 %), which is statistically significant (P <0.05). Conclusion: According to the results of the study, lung CTscan findings along with some clinical and laboratory findings can help differentiate COVID-19 pneumonia from influenza pneumonia, which is very important in faster diagnosis and timely treatment of both diseases.